An Overview of Informed Consent in Dentistry in Malaysia - Haniwarda Yaakob (UiTM Press, 2023)
Introduction: Obtaining informed consent from patients is a fundamental legal and ethical element that is required of dental practitioners. From routine procedures such as dental filling or scaling to more complicated procedures such as oral surgeries, it is imperative that patients' informed consent be acquired. Failure to procure a valid consent from patients prior to embarking on any dental treatment may cause several potential legal repercussions against dental practitioners. This paper, thus, seeks to discuss the issue of informed consent with particular reference to dental practice. It begins with an explanation on the laws governing informed consent in Malaysia. Then, an analysis on the ethical aspect behind the need to obtain patient's consent, namely patient autonomy is provided. This is followed with a discussion on the potential legal consequences for failure to obtain informed consent, limiting to civil actions only. Methods: This is a descriptive paper that adopts legal doctrinal and qualitative method of analysis. Conclusion: The precondition of obtaining patients' informed consent is a fundamental aspect in dental practice both for patients and dental practitioners.